Hewettite ZnV6O16 ⋅ 8H2O with Remarkably Stable Layers and Ultralarge Interlayer Spacing for High‐Performance Aqueous Zn‐Ion Batteries. Issue 1 (21st October 2022) - Zhu, Kaiyue; Jiang, Weikang; Wang, Zhengsen; Li, Weijian; Xie, Weili; Yang, Hanmiao; Yang, Weishen
Abstract: Aqueous Zn‐ion batteries (ZIBs) are promising candidates for grid‐scale energy storage because of their intrinsic safety, low‐cost and high energy‐intensity. Vanadium‐based materials are widely used as the cathode of ZIBs, especially A2 V6 O16  ⋅ nH2 O (AVO, A=NH4 +, Na, K). However, AVO suffers from serious dissolution, phase transformation and narrow gallery spacing (∼3 Å), leading to poor cycling stability and rate capability. Herein, we unveiled the root cause of the performance degradation in the AVO cathode and therefore developed a new high‐performance cathode of ZnV6 O16  ⋅ 8H2 O (ZVO) for ZIB. Through a method of ion exchange induced phase transformation, AVO was converted to hewettite ZVO with larger gallery spacing (∼6 Å) and more stable V6 O16 layers. ZVO cathode thus constructed delivers a high capacity of 365 and 170 mAh g −1 at 0.5 and 15 A g −1, while 86 % and 70 % of its capacity are retained at 0.5 A g −1 after 300 cycles and at 15 A g −1 after 10000 cycles, substantially better than conventional AVO. Abstract : Via an ion exchange induced phase transformation, A2 V6 O16  ⋅ nH2 O (AVO, A=NH4 +, Na, K) was transformed to hewettite BV6 O16  ⋅ 9H2 O (B=Zn, Mg, Ca, Cu), accompanied by reconstruction of the layers and expansion of interlayer spacing. Benefiting from the remarkably stable layers and ultralarge interlayer spacing, the ZnV6 O16  ⋅ 8H2 O cathode exhibits an ultralong life and ultrahigh rate capability in aqueous Zn‐ion batteries, substantially better than AVO.